Identification and functional characterization of olfactory indolergic receptors in Drosophila melanogaster. (December 2021) - Ruel, David M.; Vainer, Yuri; Yakir, Esther; Bohbot, Jonathan D.
Abstract: Indole-sensitive odorant receptors or indolORs belong to a mosquito-specific expansion as ancient as the Culicidae lineage. Brachyceran flies appeared to lack representative members of this group despite the importance of indolics in this important group of dipterans. To explore whether indolORs occur in other brachyceran species, we searched for candidate indolORs in Drosophila melanogaster . Using phylogenetic tools, we show that D. melanogaster OR30a, OR43a, and OR49b form a distinct monophyletic lineage with mosquito indolORs. To explore a potential functional orthology with indolORs, we expressed these three Drosophila ORs in Xenopus laevis oocytes and measured their responses to a panel of indolic compounds. We provide evidence that OR30a, OR43a, and OR49b exhibit high sensitivity to indoles. Along with the recent discovery of indolORs in the housefly Musca domestica, our findings suggest that indolORs are a widespread feature of the peripheral olfactory systems of Diptera. Graphical abstract: Image 1 Highlights: Drosophila melanogaster OR30a, OR43a and OR49b are olfactory indolergic receptors. Olfactory indolergic receptor occurs outside the mosquito clade. The emergence of indolORs precedes the Culicidae-Brachycera split.